PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERMUATAN SATUA BALI PADA MATERI INTERAKSI SOSIAL DI MASYARAKAT UNTUK SISWA KELAS IV SEKOLAH DASAR DI GUGUS V KECAMATAN BULELENG - Luh Anggariyanti; Wati, Ni Nyoman Kurnia; Ni Putu Candra Prastya Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning Social Interaction in Society in Elementary Schools requires learning me-dia capable of providing meaningful, contextual, and engaging learning experi-ences. Preliminary observations conducted in Cluster V of Buleleng District indi-cated that learning activities were still dominated by conventional teaching methods and textbook-based instruction. This condition affected students’ motivation and learning outcomes. In addition, local cultural integration in learning activities re-mained limited. This study aims to develop interactive learning media integrated with Balinese folktales (Satua Bali) for the topic of Social Interaction in Society among fourth-grade elementary school students. The study employed a Research and De-velopment (R&D) approach using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The prod-uct developed is an interactive digital learning medium integrating social interaction materials with Satua Bali as contextual learning resources. The media includes texts, illustrations, audio narration, animations, and interactive exercises. The de-veloped media is expected to improve students’ understanding of social interaction concepts, increase learning motivation, and strengthen local cultural values and character education..Keywords: Interactive Learning Media, Satua Bali, Social Interaction, Elementary School.